The study of protein recruitment to UV-induced DNA lesions can be distorted by photoconversion of DNA dyes like Hoechst or DAPI [version 1; referees: 1 approved, 2 approved with reservations] - Verena Hurst; Susan M. Gasser (F1000Research, 2019)
A common approach used to assess DNA repair factor binding in mammalian cells is to induce DNA damage with a UV laser and follow the movement of GFP-tagged proteins to the site of damage. Often these measurements are performed in the presence of the blue DNA intercalating dye Hoechst or DAPI, which is used to label nuclear DNA. A UV-induced switch of Hoechst and DAPI from a blue-light to a green-light emitter will give a false positive signal at the site of damage.  Thus, photoconversion signals must be subtracted from the overall green-light emission to determine true recruitment. Here we demonstrate the photoconversion effect and suggest control experiments to exclude false-positive results.